Detection Of HPV-DNA In Cervical And Urethral Scrapings Using Hybrid Capture 2 And Nested-PCR And Their Correlation With Cytomorphology - Othman, Norodiyah (2010)

(untitled)
Human papillomavirus (HPV) infection is a causative agent for development of cervical cancer. This study aims to detect the presence of HPV in routine pap smears of women who attended Hospital Kota Bharu, Hospital Universiti Sains Malaysia and Hospital Kuala Terengganu. The cervical sample from each woman was in two forms (split sampling); conventional smear (CP) and ThinPrep® smear (TP). These women were given a questionnaire to determine the risk factors for cervical cancer development.